Halloween horror - Clemen Gina D. B.; Benvenuto, Mario (Genoa [Italy] : Black Cat, 2003)
Presents a series of stories about the Salem witch trials, the origins of Halloween, and other spooky tales, with vocabulary words, illustrations, and activities.
Compact disc.
Contains KET-style and Trinity-style exercises.
Young Adult
System requirements stated.
Keywords: Readers (Elementary).; Readers; CD-ROMs.; Compact discs; Reading materials; CD-ROMs.; Compact discs